Spatial navigation deficit in amnestic mild cognitive impairment - Hort, Jakub (National Academy of Sciences, 2007)
Patients with Alzheimer's disease (AD) frequently have difficulties with spatial orientation in their day-to-day life. Although AD is typically preceded by amnestic mild cognitive impairment (MCI), spatial navigation has not yet been studied in MCI. Sixty-five patients were divided into five groups: probable AD (n = 21); MCI, further classified as amnestic MCI single domain (n = 11); amnestic MCI multiple domain (n = 18), or nonamnestic MCI (n = 7), and subjective memory complaints (n = 8). These patients, together with a group of healthy control subjects (n = 26), were tested by using a four-subtests task that required them to locate an invisible goal inside a circular arena. Each subtest began with an overhead view of the arena showed on a computer monitor. This was followed by a real navigation inside of the actual space, an enclosed arena 2.9 m in diameter. Depending on the subtest, the subjects could use the starting position and/or cues on the wall for navigation. The subtests thus were focused on allocentric and egocentric navigation. The AD group and amnestic MCI multiple-domain group were impaired in all subtests. The amnestic MCI single-domain group was impaired significantly in subtests focused on allocentric orientation and at the beginning of the real space egocentric subtest, suggesting impaired memory for allocentric and real space configurations. Our results suggest that spatial navigation impairment occurs early in the development of AD and can be used for monitoring of the disease progression or for evaluation of presymptomiatic AD.